2019
DOI: 10.3389/fevo.2019.00426
|View full text |Cite
|
Sign up to set email alerts
|

Migration Patterns of Upland Sandpipers in the Western Hemisphere

Abstract: Our research protocols followed recommended procedures in the Guidelines to the Use of Wild Birds in Research of the Ornithological Council. We conducted our project under government permits for scientific research, including federal and state permits for live capture and tagging of wild birds, and access permits for working at facilities of the US Department of Defense and Konza Prairie Biological Station.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The importance of individuals adjusting migratory behaviors to environmental conditions is particularly evident in long-distance avian migrants that cross challenging landscapes such as deserts, oceans and mountains [19][20][21]. How migratory birds overcome ecological barriers has been studied for many species [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of individuals adjusting migratory behaviors to environmental conditions is particularly evident in long-distance avian migrants that cross challenging landscapes such as deserts, oceans and mountains [19][20][21]. How migratory birds overcome ecological barriers has been studied for many species [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…New tracking technologies can provide valuable insights into the movements of migratory shorebirds, but it is often difficult to assess whether the methods are also reducing survivorship (Olson et al, 2014 ; Senner et al, 2019 ). Estimates of survival for banded‐only birds provide a useful comparison for evaluation of different types of harness designs and tracking tags (Hill et al, 2019 ; Mong & Sandercock, 2007 ; Ruthrauff et al, 2019 ; Watts et al, 2019 ). Baseline estimates of survival are also useful for identifying the negative effects of habitat loss and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This extends our knowledge of shorebird species that are capable of transoceanic flights to those weighing <100 g. Typically, large shorebirds averaging ≥200 g, such as bar‐tailed godwit ( Limosa lapponica ; Battley et al, 2012; Gill et al, 2009) and bristle‐thighed curlew ( Numenius tahitiensis ; Marks & Redmond, 1994) are considered capable of extended non‐stop flights of >4000 km in distance. However, recent studies have indicated that medium‐ and light‐weight shorebirds such as upland sandpiper ( Bartramia longicauda ; mean body mass of 142 g; Hill et al, 2019) and sanderling ( Calidris alba ; mean body mass of 70 g; Conklin et al, 2017) are also capable of transoceanic flights without the need to refuel. Additionally, smaller migrants such as pectoral sandpiper ( Calidris melanotos ; mean body mass of 79 g) and white‐rumped sandpiper ( Calidris fuscicollis ; mean body mass of 42 g) that travel through the James Bay Region are known to complete long‐distance migrations without apparent refueling stops in the United States (Anderson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%